FORMATION OF SELF-EDUCATIONAL COMPETENCE OF FUTURE TEACHERS OF PRIMARY GRADES BY MEANS OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Voropay, N.A. (Pedagogy of Higher and Secondary Education, 2010)
The article opens the question of the use of informative-communicative technologies in process of formation of the self-educational competence in teachers of primary school.